A Preclinical Animal Model to Assess the Effect of Pre-existing Immunity on AAV-mediated Gene Transfer - Li, Hua; Lin, Shih-Wen; Giles-Davis, Wynetta; Li, Yan; Zhou, Dongming; Xiang, Zhi Quan; High, Katherine A; Ertl, Hildegund CJ (Molecular therapy, 2009)
Hepatic adeno-associated virus (AAV)-serotype 2–mediated gene transfer results in sustained transgene expression in experimental animals but not in human subjects. We hypothesized that loss of transgene expression in humans might be caused by immune memory mechanisms that become reactivated upon AAV vector transfer. Here, we tested the effect of immunological memory to AAV capsid on AAV-mediated gene transfer in a mouse model. Upon hepatic transfer of an AAV2 vector expressing human factor IX (hF.IX), mice immunized with adenovirus (Ad) vectors expressing AAV8 capsid before AAV2 transfer developed less circulating hF.IX and showed a gradual loss of hF.IX gene copies in liver cells as compared to control animals. This was not observed in mice immunized with an Ad vectors expressing AAV2 capsid before transfer of rAAV8-hF.IX vectors. The lower hF.IX expression was primarily linked to AAV-binding antibodies that lacked AAV-neutralizing activity in vitro rather than to AAV capsid–specific CD8+ T cells.